Influence of microstructure on the mechanical properties of thermally sprayed NiCoCrAlY coatings determined by small punch testing - Jackson, George Anthony (2018)
The development of new thermal barrier coatings (TBCs) capable of increasing the efficiency of gas powered turbines requires an understanding of the time-dependent and time-independent properties of MCrAlY bond coats. High velocity oxy-fuel (HVOF) thermal spraying was used to manufacture free-standing coatings from one commercially available CoNiCrAlY bond coat alloy powder and three experimental NiCoCrAlY powders with potential application as new bond coat alloys. All coatings were subsequently heat treated at 1100 °C for 2 h to simulate a high temperature heat treatment stage used in manufacturing coated components. X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDX) and electron back-scatter diffraction (EBSD) were used to characterise the microstructure of powders and coatings and characterise crack growth and fracture behaviour following mechanical testing.